The effects of blood flow restriction training on PAP and lower limb muscle activation: a meta-analysis - Wang, Jian; Liu, Haiyang; Jiang, Lizhu (Frontiers in Physiology, 2023)
Objective: This study aims to systematically evaluate the effects of blood flow restriction (BFR) training on lower limb muscle activation and post-activation potentiation (PAP) in athletes through a meta-analysis and discuss methods to improve instant muscle strength so as to provide a reference for training in this field. Methods: Randomized controlled trials (RCTs) that examined the impact of BFR training on muscle activation and PAP were gathered through database searches, such as CNKI, Wanfang, Web of Science, PubMed, and others. The Cochrane risk of bias tool was used to include and exclude literature. Quality evaluation and statistical analysis were conducted using ReviewManager 5.3 software, STATA 16.0, and other software programs. The sensitivity analysis and funnel plots were employed to assess result stability and publication bias. Results: In total, 18 literature studies were included with a total of 267 subjects. The meta-analysis showed that BFR could significantly improve the RMS value of lower limb muscles [SMD = 0.98, 95% CI (0.71, 1.24), and p < 0.00001]. BFR had a significant effect on the immediate explosive power of the lower limbs [SMD = 0.28, 95% CI (0.02, 0.53), and p = 0.03], but the heterogeneity was obvious (I2 = 51%). The subgroup analysis showed that different training methods may be influencing factors that lead to the heterogeneity between studies. The measurement indexes were the counter movement jump (CMJ) [SMD = 0.45, 95% CI (0.20, 0.69), and p = 0.0004], training mode to overcome body weight [SMD = 0.57, 95% CI (0.33, 0.82), and p < 0.00001], and compressive strength of 40%–60% arterial occlusion pressure (AOP) [SMD = 0.57, 95% CI (0.31, 0.83), and p < 0.0001], which reached the maximum effect and was statistically significant. Conclusion: BFR training can induce lower extremity muscle activation and PAP. Combining self-weight training with BFR exercises set at 40%–60% AOP appears to be particularly effective in inducing PAP, especially for enhancing CMJ. Furthermore, combining body-weight training with BFR is considered an effective warm-up method to improve CMJ. Systematic Review Registration: http://inplasy.com, identifier INPLASY2023100087